2019
DOI: 10.1177/1740774519862564
|View full text |Cite
|
Sign up to set email alerts
|

Detection of atypical data in multicenter clinical trials using unsupervised statistical monitoring

Abstract: Background/Aims A risk-based approach to clinical research may include a central statistical assessment of data quality. We investigated the operating characteristics of unsupervised statistical monitoring aimed at detecting atypical data in multicenter experiments. The approach is premised on the assumption that, save for random fluctuations and natural variations, data coming from all centers should be comparable and statistically consistent. Unsupervised statistical monitoring consists of performing as many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Put simply, the DIS is a weighted geometric mean of the P values of all tests performed to compare center i with all other centers. In fact, the calculation of the DIS is more complex than this formula suggests, but the technical details are unimportant here [35]. Venet et al discusses other ways of combining many statistical tests to identify data issues in multicenter trials [31].…”
Section: Central Statistical Monitoring In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Put simply, the DIS is a weighted geometric mean of the P values of all tests performed to compare center i with all other centers. In fact, the calculation of the DIS is more complex than this formula suggests, but the technical details are unimportant here [35]. Venet et al discusses other ways of combining many statistical tests to identify data issues in multicenter trials [31].…”
Section: Central Statistical Monitoring In Practicementioning
confidence: 99%
“…Experience from actual trials [29,31,32,36,39] as well as extensive simulation studies [35] have shown that a statistical data quality assessment based on the principles outlined above is quite effective at detecting data errors. Experience from actual trials suggests that data errors can be broadly classified as: Whilst some of these data errors are worse than others, in so far as they may have a more profound impact on the results of the trial, all of them can potentially be detected using CSM, at a far lower cost and with much higher efficiency than through labor-intensive methods such as source data verification and other on-site data reviews.…”
Section: Csm Findingsmentioning
confidence: 99%
“…A "data inconsistency score" (DIS) can be calculated for each center on the basis of the P-values of all statistical tests performed for this center (a row in the matrix of P-values) (Trotta et al 2019). Statisticians at the FDA have proposed two alternative ways of scoring centers, one based on a Fisher combination test and the other on a likelihood ratio test (Xu et al 2020).…”
Section: Center Scoringmentioning
confidence: 99%
“…Such central statistical monitoring has been suggested to detect fraud and other types of data errors in clinical trials [3][4][5][6]. Several examples of data discrepancies suggestive of inappropriate training, poor understanding of the protocol, sloppiness in collecting the data, and fabrication of data or fraud have been reported in the literature [5,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%